THE CONCEPT OF EDUCATOR PATIENCE IN THE PERSPECTIVE OF ISLAMIC EDUCATION PSYCHOLOGY: ACTIVE AND PASSIVE PATIENCE - Ismail Ismail (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2025)
In reality, many teachers interpret patience as a passive attitude of restraint, without reflective action in dealing with student behaviour. In contrast, education requires active, adaptive patience to cultivate students with good character and resilience. The purpose of this study is to examine the importance of patience in educators as a psychological and spiritual foundation in Islamic educational practice and to analyse and develop a conceptual understanding of the two dimensions of active and passive patience and their implications for the effectiveness of learning and character building in students within the framework of Islamic educational psychology. The research used a qualitative approach with a descriptive-analytical library research design, drawing on primary and secondary sources such as Qur’anic interpretations, educational psychology books, and contemporary research. The results and discussion show that active patience reflects self-control and spiritual adaptation in facing educational challenges, while passive patience reflects sincere acceptance of Allah’s provisions. Both are important foundations in building emotional calm, learning motivation, and the effectiveness of educational interactions in an Islamic educational environment.